Fiddler crab (Crustacea: Ocypodidae) distribution and the relationship between habitat occupancy and mouth appendages - Checon, Helio Herminio; Costa, Tânia Marcia [UNESP] (Taylor & Francis, 2017)
Sediment characteristics, especially grain size, are usually considered the most important variables affecting Uca distribution, mainly due to its close relationship with mouth appendage morphology. The aim of this study was to verify, from an assemblage perspective, if sediment is the most important variable affecting Uca species distribution, and if mouth appendage morphology (setae type and curvature) would be related to habitat occupancy. Niche metrics and null model approaches were used to assess and test the hypothesis. The relevance of spoon-tipped setae curvature to Uca distribution was verified for the first time. A fragmented mangrove area was divided into seven subareas, and sampling of crabs and environmental variables took place in June and November 2010. Of 10 species recorded for Brazil, seven were found in the study area: U. burgersi, U. cumulanta, U. leptodactyla, U. maracoani, U. rapax, U. thayeri and U. uruguayensis. Multivariate analysis showed that sediment grain size and the presence of vegetation were the most important variables explaining distribution, reinforcing results commonly obtained by univariate approaches. The overlap of habitat occupancy was generally low and no relationship between mouth appendages was found with breadth and overlap measures. Contrary to predictions, most non-random overlap values were lower than expected by chance, suggesting that interspecific competition might influence species distribution. Also, variables such as the presence of vegetation are important and influence crab distribution, limiting the potential distribution that would be predicted by mouth adaptations alone. Thus, the use of these adaptations as surrogates of fiddler crab distribution is not recommended.
Keywords: mangrove fauna; niche overlap; Uca spp. niche breadth